2015
DOI: 10.1259/bjr.20150405
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for benign disease; assessing the risk of radiation-induced cancer following exposure to intermediate dose radiation

Abstract: Most radiotherapy (RT) involves the use of high doses (.50 Gy) to treat malignant disease. However, low to intermediate doses (approximately 3-50 Gy) can provide effective control of a number of benign conditions, ranging from inflammatory/proliferative disorders (e.g. Dupuytren's disease, heterotopic ossification, keloid scarring, pigmented villonodular synovitis) to benign tumours (e.g. glomus tumours or juvenile nasopharyngeal angiofibromas). Current use in UK RT departments is very variable. This review id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 110 publications
1
55
0
4
Order By: Relevance
“…Studies have shown that intermediate‐dose (> 20 Gy) to high‐dose (> 50 Gy) radiotherapy in pediatric patients can increase secondary cancer risk, such as basal cell carcinoma, since children have enhanced radiosensitivity and expected longevity . However, low‐dose radiation has relatively low risk of both acute and long‐term toxicities and can still provide a complete remission even when aggressive markers are shown on pathology .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that intermediate‐dose (> 20 Gy) to high‐dose (> 50 Gy) radiotherapy in pediatric patients can increase secondary cancer risk, such as basal cell carcinoma, since children have enhanced radiosensitivity and expected longevity . However, low‐dose radiation has relatively low risk of both acute and long‐term toxicities and can still provide a complete remission even when aggressive markers are shown on pathology .…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that claim radiation-induced sarcomas to be more sinister in their course and having shorter latency than other RIM [19, 20]. Studies evaluating risk of RIM in intermediate dose radiation given to benign diseases indicate a very small risk but have advised caution in pediatric population in view of long latency of these tumours [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Due to the small number of affected individuals and long latency period associated with RIM, there is currently no level 1 evidence analyzing risk factors predicting the development of RIM. However, McKeown et al [21] have reviewed the existing literature and have found a trend towards increased risk of RIM with increasing dose, estimated to be 10%/Sv for high-dose rate exposure. The effect was more pronounced in children.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other groups argue that a significantly lower risk of radiogenic cancer inductionapprox. ten times less-should be adopted [49,61]. Furthermore, taken the new standard scheme with 6 × 0.5 Gy into account, these risks are additionally halved.…”
Section: Induction Of Malignanciesmentioning
confidence: 99%